Retailing Business Strategy of PT Mega Perintis Tbk as A Local Fashion Brand During Covid-19 Pandemic - Suci Thesi Siana; Jony Oktavian Haryanto (Budapest International Research and Critics University, 2022)
The COVID-19 pandemic has caused an economic downturn that has impacted the fashion retail industry, there are several phenomena caused by uncertainty that make a company to have a strategy in order to survive and keep growing. This research contains strategies taken by local companies in dealing with times of crisis and it can be concluded how important for companies to deal with uncertainties in the retail during a pandemic and by using qualitative research methods researcher try to analyzing the results of interviews with company executives starting with explanations related to companies during the pandemic, the company's efforts to survive, starting strategies to grow, innovate and expand for emerging retailing opportunities especially in local brand fashion retail. PT Mega Perintis Tbk carry out a differentiation strategy in product innovation development according to the needs of the community during the pandemic, expanding market locations by reaching street level and suburban areas and invest in digitizing the entire system to adapt to retail needs. However, retail fashion trends have been shaped by the disruptive changes and make need a focus on flexibility strategy to achieve competitive advantage and digital integration as an emerging retailing opportunity.